2001
DOI: 10.1093/jat/25.7.538
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Indication of Marijuana Use Can Be Estimated From Plasma and Urine Concentrations of  9-Tetrahydrocannabinol, 11-Hydroxy- 9-Tetrahydrocannabinol, and 11-Nor- 9-Tetrahydrocannabinol-9-Carboxylic Acid

Abstract: Current technology establishes marijuana use based upon detection of the pharmacologically inactive cannabinoid metabolite (11-nor-delta9-carboxy-tetrahydrocannabinol-9-carboxylic acid, THC-COOH) in urine. No accurate prediction of time of use is possible because THC-COOH has a half-life of 6 days. To determine if a temporal relationship between marijuana use and metabolite excretion patterns could be established, eight healthy user-volunteers (18-35 years old) smoked marijuana cigarettes containing 0% (placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 0 publications
6
51
0
1
Order By: Relevance
“…As demonstrated by Huestis et al [25], the THC-COOH plasma concentrations peaked later, and showed a long-lasting plateau followed by a slow decrease. The urinary peak times of THC and metabolites were in agreement with those found in a different study, involving smoking cannabis cigarettes which contained 3.58% THC [26].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As demonstrated by Huestis et al [25], the THC-COOH plasma concentrations peaked later, and showed a long-lasting plateau followed by a slow decrease. The urinary peak times of THC and metabolites were in agreement with those found in a different study, involving smoking cannabis cigarettes which contained 3.58% THC [26].…”
Section: Discussionsupporting
confidence: 89%
“…No consistent THCCOOH/THC ratio pattern was evident. As reported previously [26], THC-COOH showed the highest intra-and inter-ubject variability and was still detectable after 4 days as the result of a 3.58% cannabis cigarette smoked [41]. Thus, the main THC metabolite is not suitable as a urine marker for recent use.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Unfortunately, the rapid rise and decline in serum THC make it difficult to use as a marker of intoxication in the setting of real world driving. Serum must be drawn within 2 h of smoking marijuana to have a generally quantifiable concentration of THC; the psychomotor effects of marijuana, however, may exceed this time frame [43,44]. Whereas an undetectable blood alcohol concentration would effectively rule out driving under the influence of alcohol (barring the effects from a hangover), an undetectable THC concentration does not similarly rule out impairment.…”
Section: Drug Testingmentioning
confidence: 99%